"Tissue Papers" from Organ‐Specific Decellularized Extracellular Matrices. (7th August 2017) - Jakus, Adam E.; Laronda, Monica M.; Rashedi, Alexandra S.; Robinson, Christina M.; Lee, Chris; Jordan, Sumanas W.; Orwig, Kyle E.; Woodruff, Teresa K.; Shah, Ramille N.
Abstract : Using an innovative, tissue‐independent approach to decellularized tissue processing and biomaterial fabrication, the development of a series of "tissue papers" derived from native porcine tissues/organs (heart, kidney, liver, muscle), native bovine tissue/organ (ovary and uterus), and purified bovine Achilles tendon collagen as a control from decellularized extracellular matrix particle ink suspensions cast into molds is described. Each tissue paper type has distinct microstructural characteristics as well as physical and mechanical properties, is capable of absorbing up to 300% of its own weight in liquid, and remains mechanically robust ( E = 1–18 MPa) when hydrated; permitting it to be cut, rolled, folded, and sutured, as needed. In vitro characterization with human mesenchymal stem cells reveals that all tissue paper types support cell adhesion, viability, and proliferation over four weeks. Ovarian tissue papers support mouse ovarian follicle adhesion, viability, and health in vitro, as well as support, and maintain the viability and hormonal function of nonhuman primate and human follicle‐containing, live ovarian cortical tissues ex vivo for eight weeks postmortem. "Tissue papers" can be further augmented with additional synthetic and natural biomaterials, as well as integrated with recently developed, advanced 3D‐printable biomaterials, providing a versatile platform for future multi‐biomaterial construct manufacturing. Abstract : This work describes a new, chemical‐independent, comprehensive approach for fabricating tissue‐ and organ‐specific, decellularized matrix‐based biomaterials: "tissue papers" (TPs). TPs are biocompatible, bioactive, surgically friendly, and compatible with existing, new 3D‐printable biomaterials.